THE INFLUENCE OF HEALTH EDUCATION ON DROUGHT DISASTER MITIGATION KNOWLEDGE - Rahmayanti, Yeni Nur; Utomo, Wahyu; Cahyaningtyas, Anindhita Yudha (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
Disaster health education is included in disaster mitigation which aims to increase public knowledge and minimize casualties caused when a disaster occurs. School-aged children are a vulnerable group who are still unfamiliar with disaster knowledge, so there is a need for health education about disasters. The aim of the research is to determine the influence of health education on students' knowledge of drought disaster mitigation. This research uses a Pre-Experimental research type that uses a One-Group Pre-Test and Post-Test Design, and uses a total sampling technique with a sample size of 46 respondents. The results of the research before being given health education showed that 29 (63.0%) respondents were at a good level of knowledge with an average score of 10.17. The research results after being given health education increased students' knowledge level, namely 41 (89.1%) respondents had good knowledge with an average score of 11.93. The data analysis used was the Wilcoxon test, with a significance level of a=0.05, the result was r 0.000<a so that H0 was rejected and Ha was accepted. From these results it can be concluded that there is an influence of health education on students' knowledge of drought disaster mitigation.